(untitled) - Chambliss, William J. (New York, 2012)
Well-known researchers and academics, William Chambliss and Aida Hass help students make the vital connections they need to understand and succeed in criminology. Criminology: Connecting Theory, Research, and Practice demonstrates the value of understanding the relationship between criminological theory, research, and practice in the study of crime and criminal behavior. In doing so, it better equips students to comprehend the role of criminological theory and research in the development of criminal justice policies and practices.
Keywords: Tội Phạm,Criminology